The multiple–level system of John Updike’s novel «The Centaur» and its pre–translation analysis. (Eurasian Journal of Philology Science and Education, 2015)
This article is dedicated to consideration of the novel «The Centaur» from the point of view of functional complexity of its structure. The purpose of this article is the structural analysis of level components of the original text for further consideration of the deep meaning of the novel for identifying the author’s intention and his sphere of concepts. The creative work of J.Updike is characterized by the activity of various topics touching upon the problem of understanding human values. In his works, the writer hadn’t just used different mythological images, themes and motives, and carried their modernist reinterpretation, portraying goodies of his works in terms of the highest spiritual perfection. The ancient Greek myths and social reality intertwine in the structure of his creative work. At the level of poetics his creativity is characterized by use of structural and substantial elements of the myth, game on a joint of illusions and reality, by appliance of cyclic model of time, and also by the contrast image of the western and eastern religious and philosophical ideology penetrated by traditionalism, negation of progress, orientation to the past and belief in predeterminacy of destiny.
Keywords: sphere of concepts; mythological image; pre-translation analysis; prospection; defisation; archetype; modernist reinterpretation